Letter from James Curtis Booth to A. L. Snowden, March 12, 1879 - Booth, James Curtis (1879)
James Curtis Booth (1810-1888) sends Archibald Loudon Snowden (1835-1912), Superintendent of the United States Mint at Philadelphia from 1879 to 1885, Booth's monthly report in which there is a marked loss of silver during daily meltings. Booth speculates upon the reason and suspects a clerical error.
Keywords: Booth, James Curtis, 1810-1888; Metals--Refining; United States Mint; Mint of the United States; Snowden, Archibald Loudon, 1835-1912